Comparison of fatigue performance of TC4 titanium alloy welded by electron beam welding and laser welding with filler wire. Issue 4 (20th January 2022) - Long, Jian; Zhang, Lin‐Jie; Zhang, Li‐Xu; Wu, Jun; Zhuang, Ming‐Xiang
Abstract: This research compared high‐cycle fatigue (HCF) performances of joints of Ti–6Al–4V titanium (TC4) alloy with the thickness of 30 mm welded by vacuum electron beam welding (EBW) and laser welding with filler wire (LWFW) (hereinafter referred to as EBW and LWFW joints). Under test conditions, the fatigue strength of the LWFW joint is only 65% that of the EBW joint. Based on analysis, the main reason is that a larger microhardness gradient is present in the LWFW joint. The average microhardness of the weld metal (WM) of the LWFW joint is 41 HV lower than that of base metal (BM). A lot of punctate β phases in the WM of the LWFW joint may be an important reason for its softening. The research results provide data supports for the application of the EBW and LWFW of Ti alloy in the field of aviation manufacturing. Highlights: Compared high‐cycle fatigue performances of joints of TC4 welded by EBW and LWFW. The fatigue strength of the LWFW joint is only 65% that of the EBW joint. The tensile strength of the LWFW joint is 96% that of the EBW joint. The WM of the LWFW joint is weakened, and it lowered than that of the EBW joint.